TOXICITY TEST OF Eusideroxylon zwageri BARK EXTRACT BASED ON KIDNEY HISTOPATHOLOGY OF BLEEDING AND NECROSIS - Namira Fathya Salsabila; I Wayan Arya Krishnawan Firdaus; Yusrinie Wasiaturrahmah; Juliyatin Putri Utami; Bambang Setiawan (FKG ULM, 2025)
Background: Ironwood plant (Eusideroxylon zwageri) can potentially be an herbal medicine that accelerates wound healing because of the antioxidant compounds contained in it. The dominant compounds contained in ironwood bark are flavonoids 30.48 mgCE/g, phenolics 31.28 mgCE/g, and proanthocyanidins 183.3 mgCE/g. Before used as an herbal medicine, it is necessary to do an acute toxicity test on ironwood bark at doses of 1.250 mg/kgBW, 2.750 mg/kgBW, and 4.750 mg/kgBW to consider the right dose. Acute toxicity tests can be seen using histopathological appearance in the kidney based on bleeding and necrosis. Purpose: Determine the toxic effects of giving Eusideroxylon zwageri doses of 1.250 mg/kgBW, 2.750 mg/kgBW, and 4.750 mg/kgBW on the kidneys of Wistar rats (Rattus norvegicus) based on bleeding and necrosis in histopathological appearance. Method: Research is true experimental and posttest-only with control design. The study was divided into a control group given aquades and a treatment group given ironbark extract dose of 1.250 mg/kgBW, 2.750 mg/kgBW, and 4.750 mg/kgBW as much as 1 ml given 2 times a day orally for 14 days. Results: The percentage of histopathological appearances of bleeding and necrosis score is 1 or mild. Analysis of bleeding and necrosis did not show significant differences of ironwood bark extract doses of 1.250 mg/kgBW, 2.750 mg/kgBW, and 4.750 mg/kgBW. Conclusion: There were no toxic effects of ironwood bark extract doses of 1.250 mg/kgBW, 2.750 mg/kgBW, and 4.750 mg/kgBW on the kidney organs of wistar rats based on bleeding and necrosis in histopathological appearances.